The design of aesthetic interaction: towards a graceful interaction framework - Wan Norizan, Wan Hashim; Nor Laila, Md Noor; Wan Adilah, Wan Adnan (ACM, 2009)
The growth of techno-dependency and the proliferation of creative engagement have spurred research towards the creation of human values through digital engagement. Against the backdrop of technology evolution, research on human computer interaction (HCI) has begun to explore dimensions of human value derived from the aesthetics of interaction. This desire for beauty aligns to the Maslow's hierarchy of human needs which acknowledge that humans needs aesthetic satisfaction to realize self-actualization. However in the past, the main focus of aesthetics in HCI research was on visual beauty of the user interface. To further explore new forms and perspective of aesthetics of interaction, we present the notion of graceful interaction. In this paper, we present the theoretical understanding derived from the multidisciplinary areas of human basic movement, aesthetics and interaction design into a graceful interaction phenomenon of interactive interface as an attempt to build the foundations for the graceful interaction framework. We also argue that the aesthetics of human movement can be applied to the online environment and illustrates how the movement paradigm and can be aligned and mapped into user experience interaction design. Based on these theoretical understandings, several theoretical propositions are formed to describe the aesthetics dimensions of graceful interaction.